Making your way as an academic paediatric trainee in the UK. Issue 1 (4th December 2013) - Brown, Chrysothemis C; Apps, John R; Davies, Gwyneth; Ware, Nicholas; Fisher, John; Winyard, Paul J D
Abstract : A career path in academic paediatric medicine is an extremely rewarding one, and while not traditionally considered an academic specialty, it offers a wealth of exciting research opportunities. Developing academic paediatrics is becoming increasingly important, as recently reviewed in the Royal College of Paediatrics and Child Health (RCPCH) Turning the Tide report, 1 and developing future leaders in academic paediatrics is a key goal of the academic training pathways. Strategies are being implemented to ensure that the enthusiasm of academic trainees is maintained, and their development into future leaders is secured. 2